(untitled) (مجلة جامعة دمشق للعلوم التربوية والنفسية, 2026)
This research aimed to identify the degree to which secondary school English teachers in Syria employ artificial intelligence applications, and to uncover differences in use based on the following variables: gender, academic qualifications, years of experience, and training courses. The research used a descriptive-analytical approach. A questionnaire covering five teaching areas (planning, implementation, evaluation, communication with students, and barriers to employing AI in teaching) was administered to a sample of 87 male and female teachers. The results showed that the level of usage was moderate, and statistically significant differences were found attributable to the variables of academic qualifications and years of experience. However, no statistically significant differences were recorded attributable to gender and training variables. Based on the results, several recommendations were made, including the need to train teachers on the use of artificial intelligence applications, providing a supportive and technically equipped school environment, and conducting subsequent studies on the effectiveness of artificial intelligence in developing language skills.